2018
DOI: 10.1177/1945892418793470
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Immunoglobulin A, E, and G4 Levels Specific to Dermatophagoides pteronyssinus in Allergic Rhinitis Patients Treated With Subcutaneous Immunotherapy

Abstract: This study shows that allergen-specific IgE levels are increased in the saliva of sensitized patients, suggesting that measuring salivary IgE testing should be further considered for the diagnosis of AR. Moreover, allergen-specific IgA and IgG4 in the saliva, which may play protective roles against allergy, may serve as objective indicators for evaluating treatment response to SCIT. However, none of the immunoglobulin reflects subjective symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
1
7
1
Order By: Relevance
“…Being the main allergen component toward which children are sensitized, IgA antibodies in saliva specific for Phl p 1 were significantly higher in individuals treated with GRAZAX ® for 3 years compared to the control group. This is in line with findings from a mixed age group SCIT cohort of house dust mite allergic individuals, in which salivary levels of Der p 1–specific IgA were increased in actively treated subjects . Additionally, in the present study we observed a sustained effect 2 years after treatment cessation, suggesting that B cells have become IgA producers in the local immune environment and possibly remained as memory cells after the treatment ended.…”
Section: Discussionsupporting
confidence: 92%
“…Being the main allergen component toward which children are sensitized, IgA antibodies in saliva specific for Phl p 1 were significantly higher in individuals treated with GRAZAX ® for 3 years compared to the control group. This is in line with findings from a mixed age group SCIT cohort of house dust mite allergic individuals, in which salivary levels of Der p 1–specific IgA were increased in actively treated subjects . Additionally, in the present study we observed a sustained effect 2 years after treatment cessation, suggesting that B cells have become IgA producers in the local immune environment and possibly remained as memory cells after the treatment ended.…”
Section: Discussionsupporting
confidence: 92%
“…347 This makes it a unique finding, as it is the first time anyone has successfully measured grass pollen-specific IgA-antibodies in saliva, which poses certain challenges as a study matrix. Moreover, although other studies have shown elevations of house dust mite-specific salivary IgA-antibodies upon SCIT in adults 348 , this is the first study to show corresponding elevations of timothy grass pollen-specific IgA in saliva from children and adolescents upon SLIT treatment. Upon further examination of these level over time in children treated with GRAZAX ® , a significant difference was observed between the time of inclusion and after three years of treatment, but not later ( Figure 21B).…”
Section: Paper IIIcontrasting
confidence: 49%
“…Allergenspecific IgA2 is increased by AIT, but in contrast to IgG 4 , these differences become only apparent 2 years after initiation of the treatment (16). IgA together with IgE and IgG 4 is also present in salivary fluids and could be particularly interesting for sublingual immunotherapy (17).…”
Section: Tracking Allergen Vaccinationmentioning
confidence: 99%